Preparation and evaluation of chitin-acrylic acid graft copolymer for waste water treatment. 1. Graft copolymmerisation of acrylic acid onto chitin - Phan, Thị Bích Hạnh (2020)
A graft material based on shrimp chitin and acrylic acid (AA) has been successfully prepared in an aqueous suspension using chitin thiocarbonate-Fe(II)-hydrogen peroxide redox system as an initiator. The optimum conditions for graft copolymerization of AA into chitin were studied by observing the effect of reaction conditions, such as temperature, on the graft yield. The graft copolymer was characterized by infrared spectroscopy and thermal analysis (TGA and DSC)